The Impact of Self-Advocacy Instruction in Shaping the Self-Awareness of Students with Learning Disabilities - Chambers, Alex (The Center for Disability Studies and Services Brawijaya University, 2025)
Self-advocacy skills are essential for students with disabilities to effectively communicate their needs and obtain necessary accommodations, which are crucial for their academic success and independence. Despite the importance of these skills, students with high-incidence disabilities, including learning disabilities (LD) and attention-deficit/hyperactivity disorder (ADHD), often enter the postsecondary education environment lacking the self-advocacy skills required to request accommodations. This study aimed to evaluate the impact of self-advocacy instruction using the Self-Advocacy and Conflict Resolution (SACR) training on the self-awareness of college students with LD and ADHD regarding their self-advocacy knowledge and skills. Participants were three first or second-year college students with high-incidence disabilities who had minimal experience requesting academic accommodations. Using a pre/post survey, the study measured participants' perceptions of their self-advocacy abilities before and after instruction. The results demonstrated a significant increase in participants' self-reported confidence and skills across several domains: self-identification, requesting and using accommodations, communication, and conflict resolution. Potential implications for self-advocacy instruction are discussed.